PREPARATION, CHARACTERIZATIONS AND MODIFICATION OF Ni-Pd/NATURAL ZEOLITE CATALYSTS - Wega Trisunaryanti; Endang Triwahyuni; Sri Sudiono (Universitas Gadjah Mada, 2005)
Preparation, and modification of Ni-Pd/natural zeolite as well as their characterizations had been carried out. The aim of this research for the fututure is to prepare the best characters catalyst for the conversion of waste plastics fraction to gasoline fraction (C5-C12 hydrocarbons). The preparation of catalysts was performed by reacting a natural zeolite with the precursor of Ni(NO3)2. 9H2O and PdCl2 in an ammonia solution (25%). The modifications were performed by varying the rasio of Ni/Pd loaded to the zeolite, whereas the Pd was previously loaded and total metal content was 1 wt.% based on the zeolite. The characterization of catalysts included determination of acidity gravimetrically by adsorption of ammonia or pyridine vapour base method, metal content by Atomic Adsorption Spectrophotometer (AAS) and X-ray Fluoresence (XRF) and crystallinity by X-ray Diffraction (XRD). The treatment of catalysts using Etilene Diamine Tetra Acetic acid (EDTA) was performed to study the metal distribution on the outer or inner surface of the zeolite. The characterization results showed that the loading of metals to the zeolite increased its acidity and decreased its spesific surface area, however, did not defect its crystallnity. The metals loaded on the zeolite were distributed inside the pore and at outer surface of the zeolite. For all catalyst samples, the acidities determined using ammonia were higher than those of pyridine, and the acidities determined before the EDTA treatment was lower than those after the treatment. Metal contents of the zeolite before the EDTA treatment were higher than those after the treatment. The EDTA treatment enhanced the crystallinity of the sampel. The relationship between the metal rasio towards the acidity of the catalyst samples were in variation. Catalyst samples produced in this research have good characters, thus promisingly can be used for conversion process of waste plastics to gasoline fraction.